A Comparative Study of Literature Based on Mathematical Statistics in Big Data Environment. Issue 3 (October 2020) - Tang, Xu; He, Xueyun
Abstract: Large data environment, clustering technology has become a powerful tool for information retrieval and text mining. The essence of it is to set up a target and divide a group of objects into different groups according to the similarity. This process can set the target as similar elements in the same group, or different groups of different elements, thus achieving different purposes is a kind of undirected learning research method. This paper compares the two literature by using the frequency and clustering of the computer mathematical statistics, and clearly shows that the key to achieving harmony is to build a good society.